Transformation of Social Values in the Problem Based Learning Model in Mathematics Learning - Muhammad Tamrin; Muamar Asykur; Dian Meiliani Yulis (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to analyze the transformation of social values ​​through the Problem Based Learning (PBL) model, its impact on students' understanding of social values, as well as supporting and inhibiting factors in mathematics learning. This study uses a qualitative approach with a case study type conducted at SDI Liaganda No. 120 Kepulauan Selayar. Research informants consisted of sixth grade students as the main informants and two mathematics teachers as key informants. Data collection techniques were carried out through interviews, observations, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that: (1) the transformation of social values ​​occurs through group interactions, student activeness, reflection and presentations, and the role of teachers as facilitators; (2) the application of PBL has a positive impact on students' understanding of social values, marked by an increase in understanding of the meaning of social values, changes in social attitudes, empathy and tolerance, and social communication skills; (3) supporting factors include a conducive learning environment and the role of teachers, while inhibiting factors include differences in student abilities and characters as well as material difficulties and group dynamics.